KNOWLEDGE AND ATTITUDES OF FARMER TOWARDS BIOSECURITY IN CLOSE HOUSE BROILER FARMS IN SUSUT DISTRICT, BANGLI, BALI - Yamanik, Komang Sri; Suada, I Ketut; Sudisma, I Gusti Ngurah (Buletin Veteriner Udayana, 2025)
Biosecurity in closed-house broiler farming systems is crucial for disease prevention and ensuring animal health and welfare. The closed-house system maintains strict environmental control of temperature, ventilation, and external access restrictions. This study aimed to evaluate farmers' knowledge and attitudes regarding biosecurity in closed-house systems. A census-based survey was conducted through door-to-door interviews using questionnaires with all 30 closed-house broiler farmers in Susut District, Bangli Regency, Bali. Results showed 90% of respondents (27 farmers) demonstrated good biosecurity knowledge and attitudes, while 10% (3 farmers) showed deficiencies. These findings indicate that most farmers have properly implemented biosecurity measures. It is recommended that farmers maintain consistent biosecurity practices, while relevant agencies should enhance education through outreach programs to strengthen understanding, particularly among less compliant farmers.